2019
DOI: 10.1186/s12874-018-0639-y
|View full text |Cite
|
Sign up to set email alerts
|

An application of a pattern-mixture model with multiple imputation for the analysis of longitudinal trials with protocol deviations

Abstract: BackgroundThe benefit of a given treatment can be evaluated via a randomized clinical trial design. However, protocol deviations may severely compromise treatment effect since such deviations often lead to missing values. The assumption that methods of analysis can account for the missing data cannot be justified and hence methods of analysis based on plausible assumptions should be used. An alternative analysis to the simple imputation methods requires unverifiable assumptions about the missing data. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…The study used child mortality records data from the 2014 Ghana Demographic and Health Survey (2014GDHS). The data used for the analyses in this paper consist of 5884 complete cases [ 29 31 ] with 7 potential risk factors of child mortality. Analyses in this paper were carried out using the STATA software.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study used child mortality records data from the 2014 Ghana Demographic and Health Survey (2014GDHS). The data used for the analyses in this paper consist of 5884 complete cases [ 29 31 ] with 7 potential risk factors of child mortality. Analyses in this paper were carried out using the STATA software.…”
Section: Discussionmentioning
confidence: 99%
“…The first limitation of the study is that the authors were unable to adjust for potential risk factors that were not collected during the data collection process since the authors used secondary data. Second, the study could not utilize most risk factors because they have most of their values missing [ 29 31 ]. Third, because this study receives no funding, the authors were unable to raise funds for the collection of data on potential risk factors that were not considered during the survey or considered during the survey but could not be used because they have almost all their values missing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analyses in this paper then adjusted for risk factors of HIV testing in order to identify significant determinants of one's decision to ever test for HIV. However, the analyses in this paper are based on 1,757 persons since some of the risk factors of HIV testing have missing values [19] [20]. Ethical approval and consent to participate statements can be found on:…”
Section: Study Setting and Data Sourcementioning
confidence: 99%
“…In this study, we focused on individual birth record data, obtained from the respondents during the survey. We observed that some of the individual records have missing values [15][16][17], and hence, analyses were restricted to only the complete cases [17]. The complete data consist of 6,525 individuals who provided responses on how long it takes for them to give birth to their first child after marriage.…”
Section: Study Setting and Datamentioning
confidence: 99%